Revitalisasi Nilai Akhlak Ijtima’iyyah dalam Kurikulum Pendidikan Islam di MI/SD - Sandra Dyah Asmawati; Siti Masyithoh (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to examine efforts to revitalize social moral values in the Islamic Education curriculum at the elementary school level (MI/SD). The background of this study is driven by the urgency to integrate social values into the learning process, so that they are not merely part of the curriculum document but can also be actualized in daily educational practices. The approach used is a literature review, examining various references related to the development and implementation of moral values in the context of basic education. The results of the study indicate that the revitalization of social moral values has the potential to revive the spirit of solidarity, concern for others, and social responsibility among students. The implications of this research point to the importance of designing a more contextual and inspiring curriculum, so that students not only understand moral concepts theoretically but also internalize them in their social lives. Thus, a harmonious and supportive school environment can be effectively established.